2000
DOI: 10.1021/ja001439u
|View full text |Cite
|
Sign up to set email alerts
|

A Novel β-Directing Fructofuranosyl Donor Concept. Stereospecific Synthesis of Sucrose

Abstract: A new concept for the construction of β-D-fructofuranosides based on the idea of locking the anomeric CH 2 OH group to the R-side through an internal bridge to the 4-hydroxyl group is presented. Thioglycoside fructose donors containing an internal 1,4-O-(1,1,3,3-tetraisopropyldisiloxane-1,3-diyl) (TIPS) acetal bridge have been constructed and used in glycosylations with dimethyl(thiomethyl)sulfonium triflate (DMTST) as promoter. The couplings were stereospecific to give β-D-fructofuranosyl disaccharides in hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 18 publications
1
24
0
1
Order By: Relevance
“…However, Oscarson and Sehgelmeble have developed thioglycosides 80-82 ( Fig. 19) as donors for the steroselective synthesis of these glycosidic linkages (102,103). Although 80-82 are conformationally-restricted species, they were designed not as precursors to rigid reactive intermediates that would react in a stereoelectronically-favored manner.…”
Section: G Use Of Conformationally-restricted Donorsmentioning
confidence: 99%
“…However, Oscarson and Sehgelmeble have developed thioglycosides 80-82 ( Fig. 19) as donors for the steroselective synthesis of these glycosidic linkages (102,103). Although 80-82 are conformationally-restricted species, they were designed not as precursors to rigid reactive intermediates that would react in a stereoelectronically-favored manner.…”
Section: G Use Of Conformationally-restricted Donorsmentioning
confidence: 99%
“…A few examples of their stereoselective synthesis have been reported, including the formation of b-mannosidecontaining 1,1 0 -disaccharides 22 by use of cyclic tin acetals, 23,24 a,a-trehalose 25 by use of intramolecular aglycon delivery 26 and the preparation of sucrose. 27,28 Cook et al reported the stereoselective synthesis of b,b-trehalose by using the trichloroacetimidate method. 13 …”
Section: Introductionmentioning
confidence: 99%
“…2-4 Generally, D-fructose occurs as b-furanosyl residues, but fructosylation methods with b-selectivity are particularly limited. 3 There are two major fructosylation protocols. One is the thiofructoside glycosylation, developed by Oscarson et al, 2a which led ultimately to the first stereospecific synthesis of sucrose, which contains a b-fructofuranoside moiety, in 2000.…”
Section: Introductionmentioning
confidence: 99%
“…One is the thiofructoside glycosylation, developed by Oscarson et al, 2a which led ultimately to the first stereospecific synthesis of sucrose, which contains a b-fructofuranoside moiety, in 2000. 3 This protocol is b-stereoselective, but the donor required is costly to prepare, which limits its synthetic application. The other method uses fructosyl phosphite donors, with which good yields were obtained but the stereochemical outcome was not predictable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation